Investigating Peace Values Portrayed in Non-Government English Textbook for Senior High School Students - Arif Rahman Azis; Budi Setyono; Sugeng Ariyanto (EFL Education Journal, 2022)
Textbooks are often perceived as a platform that could greatly influence students' development in terms of character. Students could receive influential peace education through textbooks as a medium of teaching and learning. Consequently, it is absolutely necessary for any textbook used by the teacher to contain the necessary peace values required to shape students' excellent character. This study was an effort to carefully examine the portrayal of peace values in English Language Teaching (ELT) textbooks for senior high school students in Indonesia. Critical Discourse Analysis (CDA) and semiotic by Roland Barthes's (1977) framework was selected as the tool to further elaborate on the kinds of peace values presents within the English textbook and also how exactly those peace values voice out the peace values. The result showed that the selected textbook has managed to integrate the necessary peace values. However, massive imbalances of representation can be identified due to the lack of peace with nature and the abundance of social peace.